A successful model of regional healthcare information exchange in Japan: Case Study in Kagawa Prefecture - Daisuke Yamakata; Hiroki Nogawa; Masashi Ueda (International Telecommunications Society (ITS), 2011)
In this study, we focused on analysis of healthcare data exchange over the network. For the advance of broadband capability development, many governments expect online medical information exchange between medical institutions. Japanese government also has tried to deploy ICT in the healthcare field. In Japan, many healthcare ICT projects started, but almost of all the projects face many issues and failed to continue. This situation caused us to clarify the success factor of healthcare information exchange network. For inspecting the success factors, we analyzed information access of healthcare systems in Kagawa prefecture of Japan. Kagawa prefecture is one of the most advance areas for healthcare information technology. We analyzed four medical ICT projects in Kagawa prefecture: K-MIX, Critical Pathway for Diabetes, E-prescription, and PHR. In addition, we inspected characteristics of exchanged data in the network, and stakeholder involved in these projects. This analysis lets us find various types of healthcare ICT projects. Characteristic of data processed in the projects caused differences of characteristic of the projects. On the other hand, multiple systems process same data, though the project does not share the data itself. Considering various types of medical information exchanges projects, we propose classification and standard format of exchanged data according to their characteristic are critical for efficient business deployment.
Keywords: 330; e-Health; regional healthcare information exchange; EHR